Investigation of AISI Steel Vickers Hardness and Nitrogen Ion Beam Energy of a 3 kJ Plasma Focus - Arwinder, Singh; Teh, Thiam Oun; Manmeshpal, Singh; Saw, Sor Heoh; Lee, Sing (INTI International University, 2019)
INTI 3kJ Plasma Focus which produces dense hot plasmas with intense multi-radiations including x-rays, beam ions, relativistic electrons and powerful plasma streams is discussed in this paper. This device is a table top sized nuclear fusion machine producing fusion neutrons when operated in deuterium. It has many applications including energy, medical and materials. Current work on materials hardening conducted at the INTI plasma focus laboratory using nitrogen gas is briefly discussed. The methodology of the research is briefly presented as is our unique advantageous approach in integrating the laboratory measurements with analysis using the Lee code, which INTI Centre of Plasma Research plays a big role in its continuing development. An example is discussed. The beam energy obtained from the Lee codes is plotted against the average hardness obtained from the Vickers Hardness test and reveals the correlation between the energy released by the plasma beam and the hardness of the material